Синтез системы активного экранирования магнитного поля промышленной частоты - Кузнецов, Б.И.; Пелевин, Д.Е.; Бовдуй, И.В.; Котляров, Д.А. (Технічна електродинаміка, 2012)
The robust systems synthesis method of industrial frequency magnetic-field of distortions indemnification by means of magnetic-field guided sources with analytical nonlinearity in man protracted stay areas is developed. An example of the synthesized system is given.